Environmentally friendly utilization of coal gangue as aggregates for shotcrete used in the construction of coal mine tunnel - Chen, Peiyuan; Zhang, Liheng; Wang, Yonghui; Fang, Yi; Zhang, Feng; Xu, Ying (Case Studies in Construction Materials, 2021)
Coal gangue is one of the largest discharged industrial solid wastes, which is generated in the processes of coal mining and washing. To accelerate the in-situ utilization of coal gangue, this paper explored coal gangue aggregates (CGA) as the single aggregate source to prepare shotcrete used for coal mine tunnel underground in local. The effects of CGA rates and water/binder ratio (w/b) on CGA shotcrete were experimentally studied by means of the compressive strength, chloride permeability determined by electric flux method, pore structure measured by Nuclear magnetic resonance (NMR), and elastic modulus of interface transition zone (ITZ) investigated by nanoindentation. Besides, the environmental effects were discussed based on the material sustainability indicators. It was found that CGA rate played important roles in affecting the compressive strength and durability of CGA shotcrete. By increasing CGA rate from 62% to 71%, the 28d compressive strength of CGA shotcrete firstly increased and subsequently decreased independent with w/b; and the electric flux can be greatly reduced. The total porosity of CGA shotcrete with CGA rate depends on w/b. When w/b was high like 0.43 or 0.50, with the increase of CGA rate, the total porosity of CGA shotcrete decreased continuously. Due to the porous structure of CGA, it can adjust the water distribution around the aggregates and served as internal curing agents, contributing to stronger elastic modulus of ITZ. By incorporating 71% CGA, the total energy consumption and the CO2 emission of CGA shotcrete have been reduced by 24–32%, and 12–24%, respectively. This paper confirmed the feasibility of using CGA as the single aggregates source for shotcrete, which make significance to the utilization of CGA in a large scale. •Coal gangue aggregates was used as the single aggregates to prepare shotcrete.•Shotcrete with coal gangue aggregates 68% developed the highest compressive strength.•Gangue aggregates worked as a water adjustor during the hydration of cement.